Prison education in the resocialization of incarcerated individuals - Romero-Carazas, Rafael; Del Carpio-Delgado, Fabrizio; Espinoza-Casco, Roque Juan; Bernedo-Moreira, David Hugo; Morales-García, Wilter C.; Rodríguez-Asto, Renza Adriana Alexandra; Quiñones-Ormeño, Lorena Karolay (Frontiers in Education, 2025)
IntroductionPenitentiary education has been widely recognized as an essential tool for the rehabilitation and resocialization of incarcerated individuals, providing vital skills that facilitate their reintegration into society. In this context, the aim of the study was to analyze the perceptions of penitentiary education in the resocialization of incarcerated individuals among students at the National University of Moquegua.MethodologicallyA quantitative descriptive-correlational approach was adopted, using a cross-sectional design to collect data at a single point in time. The sample included 100 students selected through stratified random sampling by academic course, ensuring representativeness. Surveys were applied to assess various dimensions of prison education and its perceived effectiveness.ResultsThe results indicated a positive valuation of prison education in terms of social skills and social reintegration, although deficiencies in resources and programmatic structure were noted. The significant influence of design and institutional support on the perceived effectiveness of these programs was confirmed.ConclusionIt is concluded that there is a need to strengthen educational programs in penitentiary settings, improving their structure and resources to optimize their contribution to effective resocialization. Future research should be expanded to explore the persistence of educational effects and their adaptability to various penitentiary conditions.